Sex-Specific Mediation Effects of Workplace Bullying on Associations between Employees’ Weight Status and Psychological Health Impairments - Hans-Christian Puls (MDPI AG, 2021)
Background: Individuals with obesity face weight-related discrimination in many life domains, including workplace bullying, especially in female employees with obesity. However, associations between experiences of workplace bullying and psychological health impairments considering weight status and sex remain unclear. Methods: Within a representative population-based sample of N = 1290 employees, self-reported experiences of workplace bullying were examined for variations by weight status and sex. Using path analyses, sex-specific mediation effects of workplace bullying on associations between weight status and work-related psychological health impairments (burnout symptoms, quality of life) were tested. Results: Employees with obesity experienced more workplace bullying than those with normal weight. Workplace bullying was positively associated with psychological health impairments and partially mediated the associations between higher weight status and elevated burnout symptoms and lower quality of life in women, but not in men. Conclusions: The result that more experiences of workplace bullying were, compared with weight status, more strongly associated with work-related psychological health impairments in women, but not in men, uniquely extends evidence on sex-specific effects within weight-related discrimination. Continued efforts by researchers, employers, and policy makers are needed to reduce weight-related discrimination in work settings, eventually increasing employees’ health and job productivity.